Political and social participation of Egyptian women - Bárbara Azaola Piazza (Feminismo/s, 2004)
The Egyptian feminist movement has been regarded as having had a pioneering role in organizing the Arab feminist movement. However, as this article reveals, the last few decades here witnessed a backward trend due to various political and economic factors, which has led to lower levels of participation by Egyptian women in the political and social life of the country.